The Effect Of Product Quality And Price Perception On Customer Satisfaction On E-Commerce Platforms In Indonesia - Reni Febriani; Dihan Ahmad Baslayn; Mirza Abdi Khairusy; Alan Rakhmat Putra (Universitas Dharmawangsa Medan, 2026)
This study aims to analyze and explain the partial and simultaneous effects of product quality and price perception on customer satisfaction across e-commerce platforms in Indonesia, while identifying the most dominant predictor. Grounded in the Expectation-Confirmation Theory (ECT), this quantitative research employs a causal-associative design targeting active e-commerce users in Indonesia. Utilizing a non probability sampling technique with a purposive sampling approach, data were gathered from 400 valid respondents via an online Likert-scale questionnaire. The primary data were analyzed using multiple linear regression analysis after fulfilling all instrument tests (validity and reliability) and classical assumption requirements. The empirical findings reveal that product quality has a positive and significant partial effect on customer satisfaction, confirming that the alignment between a physical product's attributes and its digital description triggers a positive confirmation of expectations. Similarly, price perception exerts a positive and significant partial impact on customer satisfaction, highlighting the critical role of price fairness and radical information transparency for digital consumers. Simultaneously, product quality and price perception collectively account for 58.4% (R^2=0.584) of the variance in customer satisfaction. Crucially, this study resolves the ongoing research gap in existing literature by establishing that product quality is the most dominant determinant influencing satisfaction. This proves that modern digital consumers in Indonesia prioritize physical performance, specifications, and product authenticity over mere low-price comparisons. Consequently, e-commerce platform operators are strongly advised to tighten their curation systems and seller standardization to mitigate digital information asymmetry. Keywords: Customer Satisfaction, E-Commerce, Expectation Confirmation Theory, Product Quality, Price Perception.